FAKTOR-FAKTOR YANG MEMPENGARUHI HUBUNGAN PENGAWASAN BANK SENTRAL ATAS BANK KOMERSIAL (Studi kasus pada Industri Perbankan Indonesia) - Sofyan S. Harahap (Universitas Trisakti, 2003)
Indonesian banking crisis 1997 has affected Indonesian economy until to date. The cost of the crisis has burdened Indonesian economy. The cause of the crisis can be study from many aspects. Using qualitative research, mainly grounded theory method, the paper studies the control system relationship between Indonesia's central bank and commercial banks. Some elements that may affect the control system are discussed as well as the control system itself. The effect of the system may tend toward the Indonesian banking cnsis.